Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1977
DOI: 10.1055/s-0028-1097589
|View full text |Cite
|
Sign up to set email alerts
|

Two New Glycoflavones From the Roots of Phyllanthus Niruri

Abstract: The phytochemica examination of the ethyl acetate extract of the roots of P h y 11 a n t h u s n i r u r i resulted in the isolation and identification of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…Research groups in India were the first to investigate the pharmacological properties of P. niruri (Chauhan et al 1977;Thyagarajan et al 1982;Venkateswaran et al 1987). P. niruri gained worldwide attention in the late 1980s due to its activity against hepatitis B virus (Venkateswaran et al 1987).…”
Section: Introductionmentioning
confidence: 98%
“…Research groups in India were the first to investigate the pharmacological properties of P. niruri (Chauhan et al 1977;Thyagarajan et al 1982;Venkateswaran et al 1987). P. niruri gained worldwide attention in the late 1980s due to its activity against hepatitis B virus (Venkateswaran et al 1987).…”
Section: Introductionmentioning
confidence: 98%
“…Rutin Rutin (Figure 1), a flavonol glycoside comprised of the flavonol quercetin and the disaccharide rutinose, belongs to a large group of phenolic secondary metabolites of plants that includes more than 2000 different known chemicals (Chauhan et al 1977). Rutin is important because it strengthens capillaries and so is able to help people suffering from arteriosclerosis or high blood pressure (Becker et al 1985).…”
Section: Flavonoidsmentioning
confidence: 99%
“…4) Previous studies have revealed bioactivities such as antiplasmodial and antimalarial, 5,6) urolithiasis, 7) antiinflammatory, 8) and antihepatitis effects. 9) Chemical constituents such as tannins, 9,10) lignans, 11) polysaccharides, 12) alkaloid, 13) and flavonoids 14) were previously isolated.…”
Section: )mentioning
confidence: 99%